Maternal age and perinatal conditions between births at risk from 2008 to 2013 - Anna Pires Terra, Deisi Soares, Silvani Herber, Karla Pereira Machado, Louriele Wachs, Elaine Thumé (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8130-37